A behavioral mechanism underlying ecological divergence in the malaria mosquito Anopheles gambiae - Gimonneau, Geoffrey (Oxford University Press, 2010)
Disruptive selection mediated by predation on aquatic immature stages has been proposed as a major force driving ecological divergence and fostering speciation between the M and S molecular forms of the African malaria mosquito, Anopheles gambiae. In the dry savannahs of West Africa where both molecular forms co-occur, the S form thrives in temporary pools filled with rainwater, whereas the M form preferentially breeds in permanent freshwater habitats where predator pressure is higher. Here, we explored the proximal mechanisms by which predation may contribute to habitat segregation between molecular forms using progeny of female mosquitoes captured in Burkina Faso. We show that the S form suffers higher predation rates than the M form when simultaneously exposed to the widespread predator, Anisops jaczewskii in an experimental arena. Furthermore, behavioral plasticity induced by exposure to the predator was observed in the M form, but not in the S form, and may partially explain its habitat use and ecological divergence from the S form. We discuss the role of adaptive phenotypic plasticity in allowing successful colonization of a new ecological niche by the M form and highlight further research areas that need to be addressed for a better understanding of the ultimate mechanisms underlying ecological speciation in this pest of major medical importance.